Live and Recorded Music Experience in the Digital Millennium - Kjus, Yngvar (Pop Music, Culture and Identity, 2018)
This book uncovers how music experience - live and recorded - is changing along with the use of digital technology in the 2000s. Focussing on the Nordic region, this volume utilizes the theory of mentalization: the capacity to perceive and interpret what others are thinking and feeling, and applies it to the analysis of mediated forms of agency in popular music. The rise of new media in music production has enabled sound recording and processing to occur more rapidly and in more places, including the live concert stage. Digital technology has also introduced new distribution and consumption technologies that allow record listening to be more closely linked to the live music experience. The use of digital technology has therefore facilitated an expanding range of activities and experiences with music. Here, Yngvar Kjus addresses a topic that has a truly global reach that is of interest to scholars of musicology, media studies and technology studies.